2022
DOI: 10.1109/tvcg.2021.3114835
|View full text |Cite
|
Sign up to set email alerts
|

What's the Situation with Situated Visualization? A Survey and Perspectives on Situatedness

Abstract: Situated visualization is an emerging concept within visualization, in which data is visualized in situ, where it is relevant to people. The concept has gained interest from multiple research communities, including visualization, human-computer interaction (HCI) and augmented reality. This has led to a range of explorations and applications of the concept, however, this early work has focused on the operational aspect of situatedness leading to inconsistent adoption of the concept and terminology. First, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 93 publications
0
23
0
Order By: Relevance
“…AR combines real and virtual elements registered in three dimensions and provides interaction in real time. Despite decades of development, immersive analytics are still in their infancy, and no standard user interfaces have been established [125,455]. Recent reviews have further found that, for Situated Analytics, there is still a lack of an overarching definition, data representation is not unified, and the target audience is not defined [125].…”
Section: Situated Analytics Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AR combines real and virtual elements registered in three dimensions and provides interaction in real time. Despite decades of development, immersive analytics are still in their infancy, and no standard user interfaces have been established [125,455]. Recent reviews have further found that, for Situated Analytics, there is still a lack of an overarching definition, data representation is not unified, and the target audience is not defined [125].…”
Section: Situated Analytics Discussionmentioning
confidence: 99%
“…For example, situated AR has been used to teach historical events by anchoring the relevant data in the actual physical context of these events [124]. The real world can become the canvas to help users make sense of the information in situ [125]. There is a remarkable similarity between the components of DTs (blue boxes) and the generation of Situated Analytics (white boxes).…”
Section: Situated Analyticsmentioning
confidence: 99%
“…It is challenging to reconcile the world of numbers with the world of subjective experience, but not entirely impossible -for example, if an effective altruist judges that having disease A is twice as bad as having disease B, they could conclude that preventing 10,000 cases of disease A is equally desirable as preventing 20,000 cases of disease B. 9 However, getting immersed in stories takes time, and simpler formats may be needed to communicate outcomes when large datasets need to be explored, or when quick decisions are needed. A possible approach could be to first get the decision maker immersed in stories to get a visceral understanding of the ranges of experiences involved, and, at anytime after that, let them explore data using visualizations combined with visual summaries referring to those subjective experiences (a stories-then-data approach similar to Hans Rosling's magic washing machine, see Sect.…”
Section: The Challenges Of Conveying Outcomesmentioning
confidence: 99%
“…Note that in the AR relocation scenarios I discussed, the AR representations are not situated in the sense of Willett et al,[92] because they are far away from their physical referent. However, they are situated in the broader sense put forward by Bressa et al[9].…”
mentioning
confidence: 98%
“…Because of the growth in this area, many phrases are used, including: context aware, situated, in situ, embodied and embedded visualisations. While no single reference model exists, Bressa et al [91], for instance, classify the different techniques and explain that solutions consider the space they are placed within, often include a temporal variables or are time sensitive, embedded into everyday activities and put emphasis on the community of people who will create or use them. 9.…”
mentioning
confidence: 99%